The Effect of Dividend Policy, Company Size and Capital Structure on Company Value (Empirical Study on Energy Sector Companies Listed on the Indonesia Stock Exchange in 2019-2023) - Sari, Alia; Zamzami, R.Mohd. (Winter Journal: IMWI Student Research Journal, 2025)
This study is aimed at determining the influence of Dividend.Policy, Company.Size and Capital.Structure on Company Value (Empirical.study on energy sector companies listed on the.Indonesia Stock.Exchange for the 2019-2023.period). This research method utilizes a quantitative approach in a descriptive manner. The data sources used are secondary data, namely financial reports accessible on the Indonesian stock exchange in the energy sector from 2019 to 2023. In this study, the preliminary results found indicate that dividend policy provides value derived from 0.089210 < a table of 1.66940 with a significance value of 0.9292 > 0.05 so that the Dividend Policy data does not have a partial effect on the Company Value. The Company Size.has a calculated value of 2.777591 > a table of 1.66940 with a significance value of 0.0073 < 0.05 so that the Company Size partially affects the Company Value. Capital Structure has a calculation value of 1.788536 > a table of 1.66940 with a.significance value of 0.0787 > 0.05 so that the Company Size results in a partial no affect on the Company Value. And simultaneously the Dividend Policy, Company Size and Capital Structure have a Calculation value of 3.154707 > Chart 2.75 with a significance value of 0.31087 > 0.05, then simultaneously the Dividen.Policy, Company.Size and Capital.Structure have no effect on the Company Value of energy sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period.